Speckle contrast reduction of laser light using a chiral nematic liquid crystal diffuser - Hansford, D; Fells, J; Elston, S; Morris, S (AIP Publishing, 2016)
High coherence in laser light causes spatially distributed interference called speckle. In applications such as holographic projection, this undesirable side effect degrades image clarity. The current methods of speckle reduction, such as a rotating ground-glass diffuser, require additional bulky moving parts. Here, we present an alternative technology based upon a compact, electrohydrodynamic chiral nematic liquid crystal device. A spatially random phase modulation of the incident light is achieved through the electrohydrodynamic instabilities that are induced by an alternating electric field. Using a chiral nematic liquid crystal device that is doped with an ionic compound, we find that the speckle contrast can be reduced by as much as 80%.